2021
DOI: 10.3390/rs13091662
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Merged Satellite Precipitation Datasets in Monitoring Meteorological Drought over Pakistan

Abstract: The current study evaluates the potential of merged satellite precipitation datasets (MSPDs) against rain gauges (RGs) and satellite precipitation datasets (SPDs) in monitoring meteorological drought over Pakistan during 2000–2015. MSPDs evaluated in the current study include Regional Weighted Average Least Square (RWALS), Weighted Average Least Square (WALS), Dynamic Clustered Bayesian model Averaging (DCBA), and Dynamic Bayesian Model Averaging (DBMA) algorithms, while the set of SPDs is Global Precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…However, it is worth mentioning that this study did not consider the entire hyper-arid region, and drought is propagated from UIB to LIB using PCA; thus, the drought severity is comparatively lower. The results from this study are consistent with previous studies, including Adnan et al (2017) and Rahman et al (2021Rahman et al ( ) that reported 1997Rahman et al ( -2003Rahman et al ( , 2007Rahman et al ( -2008Rahman et al ( , 2012Rahman et al ( -2013Rahman et al ( , and 2017Rahman et al ( -2018 being the major drought years. These studies also reported that drought is more severe in arid and hyper-arid regions compared to humid and sub-humid regions (MIB) of the Indus Basin.…”
Section: Evaluation Of Drought In Representative Catchments Of the In...supporting
confidence: 92%
“…However, it is worth mentioning that this study did not consider the entire hyper-arid region, and drought is propagated from UIB to LIB using PCA; thus, the drought severity is comparatively lower. The results from this study are consistent with previous studies, including Adnan et al (2017) and Rahman et al (2021Rahman et al ( ) that reported 1997Rahman et al ( -2003Rahman et al ( , 2007Rahman et al ( -2008Rahman et al ( , 2012Rahman et al ( -2013Rahman et al ( , and 2017Rahman et al ( -2018 being the major drought years. These studies also reported that drought is more severe in arid and hyper-arid regions compared to humid and sub-humid regions (MIB) of the Indus Basin.…”
Section: Evaluation Of Drought In Representative Catchments Of the In...supporting
confidence: 92%
“…The use of satellite based-SPI as a meteorological drought has been used widely in many regions and many climatic zones. Suliman et al in his study revealed a good consistency in SPI time series estimated using remotely sensed precipitation data and ground stations data, with the TRMM as the champion for monitoring droughts in different climatic zones of Iraq [ 59 ]. Not only a single source of satellite-based estimated rainfall, it is also possible to combine multi sources into merged satellite precipitation datasets [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only a single source of satellite-based estimated rainfall, it is also possible to combine multi sources into merged satellite precipitation datasets [ 60 ]. A study by Rahman et al (2021) found significantly improved performance of merged satellite d in monitoring the meteorological drought [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some research [9][10][11][12][13][14] indicates the temporal versatility of the index is useful in determining the beginning and end of dry events, it allows the analysis of the impacts of droughts at different time scales, simply compared to other indices. Several authors have analyzed the advantages and disadvantages of SPI using different distributions, there are several recommended distributions for calculating the SPI.…”
Section: Introductionmentioning
confidence: 99%